Echocardiographic Features of Cardiomyopathy in Emery-Dreifuss Muscular Dystrophy. (4th February 2021) - Marchel, Michał; Madej-Pilarczyk, Agnieszka; Tymińska, Agata; Steckiewicz, Roman; Kochanowski, Janusz; Wysińska, Julia; Ostrowska, Ewa; Balsam, Paweł; Grabowski, Marcin; Opolski, Grzegorz
Abstract : Background . Emery-Dreifuss muscular dystrophy (EDMD) is a very rare type of muscular dystrophy characterized by musculoskeletal abnormalities accompanied by cardiac defects. Two most common genetic subtypes are EDMD1 due to EMD and EDMD2 caused by LMNA gene mutations. The aim of the study was to characterize and compare the cardiac morphology and function in the two main genetic subgroups of EDMD with the use of echocardiography. Methods . 41 patients with EDMD (29 EDMD1 and 12 EDMD2) as well as 25 healthy controls were enrolled in our study. Transthoracic echo with the use of a prescribed protocol was performed. Results . Highly statistically significant differences with regard to left ventricle (LV) volumes between the EDMD and the control group were found. 51% of EDMD patients had an enlarged left atrium and as many as 71% had an enlarged right atrium. The LV ejection fraction (LVEF) was significantly lower in EDMD patients than in the control group which corresponded also with a lower systolic velocity of the mitral annulus. 43% of EDMD patients had LVEF below the normal limit. Diastolic dysfunction was detected in 17% of EDMD patients. There were no significant differences between the two types of EDMD in terms of diameters and volumes of any chamber, as well as the systolic function of both left and right ventricles. Conclusions . A significant number of EDMD patients present LV dilatation and different degrees of systolic dysfunction. Dilatation of the atria dominates over ventricle dilatation. We did not present any significant differences between EDMD1 and EDMD2 in terms of the morphology and the function of the heart.